Growing snow volleyball in snow-restricted countries: A pilot study - Bahdur, Khatija; Bahdur, Zarina; Dell’Oca, Duane (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Snow volleyball is an increasingly popular sport that has been earmarked as a potential Winter Olympic discipline. However, it is not typically associated with Africa. This study provided an in-depth retrospective exploration of the experience of an African player who participated in the inaugural Snow Volleyball World Championships in 2019. Through a focused one-on-one interview, the study examined her transition to snow volleyball, the challenges she faced, and her insights into the feasibility of African participation in the sport. Drawing from both her tournament experience and her broader knowledge of the volleyball landscape, she identified key barriers such as climate, accessibility, and financial constraints, while also proposing strategies to improve feasibility. These include leveraging African players competing in European leagues, developing training opportunities in North Africa, and exploring artificial snow environments. While the study primarily focuses on the player’s personal journey, it also highlights pathways for the sport’s potential expansion in non-snow countries. This qualitative study serves as a pilot for a larger investigation into the introduction of snow volleyball to regions without winter sports traditions.